Urine tenofovir adherence testing: Perspectives of recently diagnosed South African adolescents and young adults with HIV accessing care via mobile HIV clinics - Michalina A. Montaño; Siyaxolisa Sindelo; Amanda Fata; Elzette Rousseau; Linda-Gail Bekker; Ingrid T. Katz; Paul K. Drain (PLoS ONE, 2025)
Background Adolescents and young adults (AYA) living with HIV face several challenges to engaging in HIV care, which can impact adherence to antiretroviral therapy (ART). Point-of-care (POC) diagnostics that detect tenofovir in urine may be a useful tool to support ART adherence, but perspectives from AYA in South Africa have not been explored. Methods We conducted in-depth interviews (IDIs) among young people (age 18–24) newly diagnosed with HIV in Cape Town, and a focus group discussion (FGD) with HIV care providers to understand their perspectives regarding the use of POC urine tenofovir testing to support ART adherence. Transcripts were analyzed using Dedoose, with an iterative thematic approach. Results Transcripts from 8 IDI participants and 8 FGD participants were included in the analysis. Major themes identified during analysis related to beliefs about POC urine adherence testing and recommendations for future clinical implementation. Most IDI participants indicated they would want to use the tests if clinically available, and both IDI and FGD participants believed the tests would be helpful to clinicians. Participants believed the tests could motivate people to take their ART regularly, either by reassuring them ART was present in their bodies, or to avoid the negative consequences of being found to be non-adherent. Drawbacks of POC adherence testing identified by respondents included not wanting to be caught skipping ART doses, concerns about privacy, how the test results would be explained, and adding to the amount of testing required for HIV clinical care. Conclusions AYA living with HIV in South Africa had favorable views toward POC tenofovir adherence testing and felt utilizing these tests in HIV clinical care would motivate people to remain adherent to ART.